Skin Immunosenescence and Type 2 Inflammation: A Mini-Review With an Inflammaging Perspective - Chen, Bangtao; Yang, Jing; Song, Yao; Zhang, Daojun; Hao, Fei (Frontiers in Cell and Developmental Biology, 2022)
Skin-resident stromal cells, including keratinocytes, fibroblasts, adipocytes, and immune cells including Langerhans cells, dendritic cells, T cells, and innate lymphoid cells, and their functional products work in concert to ensure the realization of skin barrier immunity. However, aging-induced immunosenescence predisposes the elderly to pruritic dermatoses, including type 2 inflammation-mediated. Inflammaging, characterized by chronic low level of pro-inflammatory cytokines released from senescent cells with the senescence-associated secretory phenotype (SASP), may drive immunosenescence and tangle with type 2 inflammatory dermatoses. The present mini-review summarizes current evidence on immunosenescence and type 2 inflammation in the skin and further focuses on future needs from an inflammaging perspective to clarify their complexity.